Association of Obsessive-Compulsive Symptoms In Patients with Other Psychiatric Morbidities In A Tertiary Care Psychiatric Setup of Rawalpindi - Ishaq , Hammad; Ahmed Shoaib; Abid Aftab; Ata Ullah; Sikandar Ali Khan; Muhammad Kamran (Pakistan Armed Forces Medical Journal, 2026)
Objectives: To determine the association of Obsessive-Compulsive Symptoms (OCS) among patients with various psychiatric morbidities at a tertiary care psychiatric setup in Rawalpindi Study Design: Cross Sectional Analytical Study Place and Duration of Study: Armed Forces Institute of Mental Health, Rawalpindi, Dec 2024 to May 2025. Methodology: Total three hundred and thirty six patients of 18–60 years diagnosed with various psychiatric disorders, diagnosed using International Classification of Disease version 10 (ICD-10) criteria were included. Obsessive-Compulsive Symptoms (OCS) were assessed using the Obsessive-Compulsive Inventory-Revised (OCI-R), a validated self-report questionnaire commonly used to measure the severity and type of OCS. Data collection involved face-to-face interviews using a semi-structured proforma, and statistical analysis was performed using SPSS version 26. Chi-square tests, ANOVA, and multiple logistic regression were used to evaluate associations between psychiatric diagnoses and OCS. Results: Total three hundred and thirty six patients were included with mean age 34.7 ± 10.6 years. Obsessive-compulsive symptoms (OCS) were identified in 108 (32.1%) with 49 (45.4%) experiencing mild symptoms, 37 (34.3%) moderate and 22 (20.3%) severe symptoms. The mean OCS severity scores differed significantly between psychiatric groups (p<0.001). Gender, residence, marital status, and clinical psychiatric diagnosis showed statistically significant associations. Conclusion: OCS are prevalent in psychiatric populations, particularly with depressive and anxiety disorders and screening for OCS is crucial for timely intervention and improved outcomes.